The principles of high voltage electric field and its application in food processing: A review - Dalvi-Isfahan, Mohsen; Hamdami, Nasser; LeBail, Alain; Xanthakis, Epameinondas (My University, 2016)
Food processing is a major part of the modern global industry and it will certainly be an important sector of the industry in the future. Several processes for different purposes are involved in food processing aiming at the development of new products by combining and/or transforming raw materials, to the extension of food shelf-life, recovery, exploitation and further use of valuable compounds and many others. During the last century several new food processes have arisen and most of the traditional ones have evolved. The future food factory will require innovative approaches food processing which can combine increased sustainability, efficiency and quality. Herein, the objective of this review is to explore the multiple applications of high voltage electric field (HVEF) and its potentials within the food industry. These applications include processes such as drying, refrigeration, freezing, thawing, extending food shelf- life, and extraction of biocompounds. In addition, the principles, mechanism of action and influence of specific parameters have been discussed comprehensively.
Keywords: Food processing; High electrostatic field; High voltage electric field; High voltage electrical discharge